The effect of mephedrone on human neuroblastoma and astrocytoma cells - Ibrahim M. Alanazi; Abdullah R. Alzahrani; Mohammad A. Alsaad; Abdulaziz L. Moqeem; Abdulmohsen M. Hamdi; Mohiuddin M. Taher; David G. Watson; M. Helen Grant (Elsevier, 2024)
Mephedrone is an illegal drug that is used recreationally. Few studies have been conducted to investigate the mechanisms by which mephedrone is harming cells. In this research, we investigated the effect of mephedrone using toxicology coupled with LC-MS/MS based metabolomics in the two CNS derived cell lines. Methods of assessment such as neutral red (NR) assay, dimethylthiazolyl diphenyltetrazolium bromide (MTT), lactose dehydrogenase (LDH) measurement, and morphology were performed to identify the effect on cell viability and to identify the best concentration to be used in a metabolomics study. A concentration of 100 μM of mephedrone was used in the metabolomic experiment because at this concentration mephedrone had induced several intracellular changes. Although there no clear indicators of cellular damage caused by mephedrone. In astrocytes there was a clear indication that cell membrane function might be impaired by depletion of ether lipids.